Genetic investigations of pneumocystis jirovecii : detection, cotrimoxazole resistance and population structure - Robberts, Frans Jacob Lourens (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Pathology. Medical Microbiology))--University of Stellenbosch, 2005.